Intimacies of Violence in the Settler Colony Economies of Dispossession around the Pacific Rim (Cambridge Imperial and Post-Colonial Studies Series, 2018)
Violence and intimacy were critically intertwined at all stages of the settler colonial encounter, and yet we know surprisingly little of how they were connected in the shaping of colonial economies. Extending a reading of 'economies' as labour relations into new arenas, this innovative collection of essays examines new understandings of the nexus between violence and intimacy in settler colonial economies of the British Pacific Rim. The sites it explores include cross-cultural exchange in sealing and maritime communities, labour relations on the frontier, inside the pastoral station and in the colonial home, and the material and emotional economies of exploration. Following the curious mobility of texts, objects, and frameworks of knowledge, this volume teases out the diversity of ways in which violence and intimacy were expressed in the economies of everyday encounters on the ground. In doing so, it broadens the horizon of debate about the nature of colonial economies and the intercultural encounters that were enmeshed within them. .